2020
DOI: 10.1136/bmjopen-2019-036365
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of self-reported financial toxicity measures in cancer survivors: a systematic review protocol using COSMIN methodology

Abstract: IntroductionDue to the higher costs associated with advancements in cancer treatment and longer duration of cancer survivorship, increasing financial toxicity has become a great threat to survivors, caregivers and public healthcare systems. Since accurate and reproducible measures are prerequisites for robust results, choosing an acceptable measure with strong psychometric properties to assess financial toxicity is essential. However, a description of the psychometric properties of existing measures is still l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…20 21 The protocol of this review was published in BMJ OPEN in 2020. 22 The registration number of the protocol in PROSPERO was CRD42021254721.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…20 21 The protocol of this review was published in BMJ OPEN in 2020. 22 The registration number of the protocol in PROSPERO was CRD42021254721.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…To include more studies published in 2021 and 2022, the end date of the search was updated to February 2022. 22 In PubMed/Medline, we searched papers in English using MeSH terms ([cancer OR neoplasms] AND ["cancer survivors" OR patient OR survivors] AND "cost of illness") combined with (cancer OR [patient* OR survivor*] AND [cost OR bill* OR expense OR productivity loss OR "out-of-pocket" OR "economic burden" OR "financial toxicity" OR "financial hardship" OR "financial burden"]). The COSMIN measurement properties filter and exclusion filter were also used in the search box.…”
Section: Search Strategymentioning
confidence: 99%
“…Assessing the Relationship between Socio-demographic, Clinical Profile and Financial Toxicity: Evidence from Cancer Survivors in Sarawak inequality of financial toxicity (FT) of cancer survivors (Zhu et al, 2020). FT describes the financial burden of cancer care faced by patients and their family members (Zafar et al, 2013).…”
Section: Research Articlementioning
confidence: 99%
“…has not yet been quanti ed in a standardized way [9][10][11] . In the long term, a lack of standardization in measurement can hinder the choice of PROMs for subsequent cross-sectional surveys and comparisons across studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of survey tools lacks consistency [9][10][11] , prior studies suggested that FT should be measured using patient-reported outcomes(PROMs)to re ect cancer survivors' thoughts, complaints and opinions that any numbers or observers cannot [10][11] . However, the development and veri cation of current PROMs vary greatly, and none of them are considered the gold standard.…”
Section: Introductionmentioning
confidence: 99%